Differential Effects of Combination of Renin-Angiotensin-Aldosterone System Inhibitors on Central Aortic Blood Pressure: A Cross-Sectional Observational Study in Hypertensive Outpatients. (8th September 2020) - Pradhan, Akshyaya; Vishwakarma, Pravesh; Bhandari, Monika; Sethi, Rishi; Narain, Varun Shankar
Abstract : Background . Central aortic blood pressure (CABP) indices, central hemodynamics, and arterial stiffness are better predictors of cardiovascular events as compared with brachial cuff pressure measurements alone. The present study is aimed at assessing the effects of different antihypertensive drug combination regimens involving renin-angiotensin-aldosterone system (RAAS) inhibitors on CABP indices in Indian patients with hypertension. Methods . This was a cross-sectional, single-center study conducted in patients treated for hypertension for >6 weeks using different treatment regimens involving the combination of RAAS inhibitors with drugs from other classes. CABP indices, vascular age, arterial stiffness, and central hemodynamics were measured in patients using the noninvasive Agedio B900 device (IEM, Stolberg, Germany) and compared between different treatment regimens. Results . A total of 199 patients with a mean age of 54.22 ± 10.15 years were enrolled, where 68.8% had hypertension for over three years and 50.25% had their systolic blood pressure SBP < 140   mmHg . Combination treatment with angiotensin II receptor blockers (ARBs) and angiotensin-converting enzyme inhibitors (ACEIs) was given to 77.9% and to 20.1% patients, respectively. The mean vascular age was higher than the actual age (58.13 ± 12.43 vs. 54.22 ± 10.15, p = 0.001 ). The SBP and diastolic blood pressure (DBP) levels in patients treated with ACEI-based combinations were lower than those in patients treated with ARB-based combinations (p < 0.05 ). The mean central pulse pressure amplification, augmentation pressure, and augmentation index were lower in patients treated with ACEI-based combinations than those treated with other treatments (p = 0.001 ). In a subgroup analysis, patients given perindopril and calcium channel blockers (CCBs) or diuretics had significantly lower CABP and pulse wave velocity than those given other treatments (p < 0.05 ). A total of 6.5% patients experienced any side effects. Conclusion . The majority of central hemodynamic parameters, including vascular age, were found to improve more effectively in patients treated with ACEIs than with ARBs. Our results indicate a gap between routine clinical practice and evidence-based guidelines in Indian settings and identify a need to reevaluate the current antihypertensive prescription strategy.